An Interpretation of the Golden Grove Gravity High in Southern New Brunswick - Gupta, V. K.; Burke, K. B. S. (Atlantic Geoscience, 1977)
The Golden Grove gravity high in southern New Brunswick is associated with mafic intrusive rocks ranging from diorite to gabbro. The anomaly was interpreted with the aid of an iterative two-dimensional gravity modelling program used in conjunction with a non-linear optimization computer package MINUIT. For minimization, the simplex method of Nelder and Mead and the variable metric method of Fletcher were used with constraint. The optimum causative body parameters indicate that the mafic intrusive mass is a sill-like (tabular) body, having a depth extent of about 1 km, with outward dipping contacts.